A study on waterproof capabilities of the bentonite-containing engineered barrier used in near surface disposal for radioactive waste - Luu, Cao Nguyen; Nguyen, Ba Tien; Doan Thi, Thu Hien; Nguyen, Van Chinh; Vuong, Huu Anh (Nuclear Science and Technology, 2017)
Study of nuclear fuel cycle in Vietnam at the aspect of domestic production, the exploitation and process of uranium ore were began. These processes generated large amounts of radioactive waste overtiming. The naturally occurring radioactive material and technologically enhanced radioactive material (NORM/TENORM) waste, which would be large, needs to be managed and disposed reasonably by effective methods. It was therefore very important to study the model of the radioactive waste repository, where bentonite waterproofing layer would be applied for the low and very low level radioactive waste in disposal site. The aim of this study was to obtain the preliminary parameters for low-level radioactive waste disposal site suitable with the conditions of Vietnam. The investigation of the ratio between soil and bentonite was interested in the safety of the uranium tailings disposal site. The experiments with some layers of waterproofing material with the ratio of soil and bentonite are 75/25; 50/50; 25/75 were carried out to test the moving of uran nuclide through these waterproofing material layers. Waterproofing layers containing bentonite combined with soil were compacted into PVC pipes. One end of the plastic tube is sealed, the other end is embedded in a solution containing uranium nuclide. Analyzing the uranium content in each layers (0,1 cm) of material pipe is to determine the uranium nuclide adsorption from solution into the material in the different ratios at the different times: 1, 2 and 3 month. The results showed that the calculated average speeds of the migration of uranium nuclide into the soil- bentonite layer are 5.4.10-10, 5.4.10-10 and 3,85.10-10 m/s and thickness waterproofing layer (for 300 years) are 4,86 m, 4,86 m and 3,63 m for layer with the ratio of soil and bentonite are 75/25; 50/50; 25/75 respectively